Roadmapping for sustainability: Evidence from an Italian-based multinational firm - Marika Arena; Davide Chiaroni (International Journal of Business Science & Applied Management (IJBSAM), 2014)
The paper analyses the process through which an Italian-based multinational company that competes in the fashion and accessories industry, developed a roadmap for its sustainability strategy. The paper discusses the use of roadmaps, as a valuable instrument for fostering change and supporting strategic thinking about sustainability. Research methodology is based on participant observation and leverages on a work conducted by the authors in tight relations with key actors in the company on a time frame of 18 months. The paper shows how the case company designed its sustainability roadmap, with the aim of posing individual behaviour at the centre of the change process. The structure of the roadmap is analysed highlighting the design choices that crucially reflect the sustainability strategy developed by the company and enabled its implementation (selection of the layers, and definition of ad hoc sub-layers). Then, examples of the actual use of the roadmap are presented and discussed, in order to pinpoint the benefits of this instrument. The results of the study highlight how firms and organisations can leverage on this type of instruments in order to collect and integrate the proposals of different individuals, aligning their actions to the corporate strategy. Furthermore, this tool can provide a basis for monitoring the results achieved through a proper set of indicators, improving a company's overall sustainability performance.
Keywords: 650; sustainability; roadmap; participant observation